THE MOVEMENT OF FEMINISM IN THE NOVEL PEREMPUAN DI TITIK NOL BY NAWAL EL SAADAWI AND THE SCRIPT OF DRAMA PELACUR DAN SANG PRESIDEN BY RATNA SARUMPAET: A COMPARATIVE LITERATURE STUDY - Fadhilah Ayu Wijayanti (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2023)
This study aims to discuss the ideology or thoughts of Nawal el Saadawi and Ratna Sarumpaet regarding feminism influencing their works. In order to achieve this goal, a descriptive qualitative method was used in this study. The source of the data comes from the novel Perempuan di Titik Nol (2022) by Nawal el Sadaawi and the drama script Pelacur dan Sang Presiden (2006) by Ratna Sarumpaet. The data used are the contents of the text and the ideas in it, the social context of the author, and other related data. Data is obtained by reading and recording information. The data were analyzed using a feminist approach. The results of the study show a picture of discrimination and injustice experienced by women in the novel Perempuan di Titik Nol by Nawal el Sadaawi and the drama script Pelacur dan Sang Presiden by Ratna Sarumpaet. These two authors highlight women's issues in their respective countries. Nawal and Ratna try to show the struggles of women from the oppression they experience through their works. These works were created as a manifestation of the feminist movement that the two authors were trying to show.